Hubungan Pengawasan Dan Motivasi Kerja Kepala Sekolah Dengan Kinerja Guru - Suhaili Suhaili (LP2M STAI Darul Kamal NW Lombok Timur, 2019)
The objective of this research are; (1) To identify The Correlation Between Head Master’s supervision towards the Performance of the Elementary School’s Teachers in Terara District. (2) To identify The Correlation Between Work Motivation of The Head Master’s towards the Performance of the Elementary School’s Teachers in Terara District. (3).To identify The Correlation Between The Head Master’s supervision and Work Motivation towards the Performance of the Elementary School’s Teachers in Terara District. Approach used in this research is quantitative approach, by the kinds of research is correlation. The population in this research are 499 consists of 48 person of the headmaster and 451 person of teachers, and the sample were taken are 307 persons consist of 30 persons of the headmaster and 277 persons of teachers. As for the data collection technique is used is conducted by questionnaire, observation and interview. Next, The technique used in analyzing the data in this research is multiple regression analysis by using SPSS version. 12.00 for Windows. The results of the research are; (1). There is correlation between Head Master’s supervision towards the Performance of the Elementary School’s Teachers in Terara District. The correlation can be seen in equal formula Ŷ = 43.628 + 0.801 X1 or sig. 0.000 < 0,05. As for the effective contribution of supervision variable toward the teacher’s performance is (0,743)2 or as big as 0,552 or (55.2 %). (2) There is correlation between The work motivation of the headmaster with the Performance of the Elementary School’s Teachers. The correlation can be seen in equal formula Ŷ = 62,006 + 0.580 X2 or sig. 0,000 < 0,05 As for the effective contribution of the work motivation of the headmaster variable toward the teacher’s performance is (0,762)2 or as big as 0,581 or (58,1 (3) There is correlation Between The Head Master’s supervision and Work Motivation towards simultaneously with the Performance of the Elementary School’s Teachers in Terara District. The correlation can be seen in equal formula Ŷ = 26,749 + 0,495 X1 + 0,383 X2 or sig. 0.000< 0,05 and Fhitung > Ftabel (35.651 > 3.34) As for the effective contribution of the supervision and work motivation of the headmaster variable toward the teacher’s performance is (0,852)2 or as big as 0,725 or (72,5 %).